The Accountants Ethics in Yemen - Al-Aidaros, Al-Hasan Mohammed Hasan (2008)
Ethics is important in any job, but it is extremely important in the accounting job. Over the years, researchers have performed numerous studies in the field of ethics in relation to the accounting profession. However, specifically in Yemen, there has been no ethical code of conduct for Yemeni accountants. This study presents the domain of Yemeni accountants' ethics. Data collected by using the questionnaire from 74 Yemeni accountants in trade companies in Sana'a city. And, this study use Interdependency Analysis to reveal the Domain of Ethical Code of Conduct for Yemeni Accountants. Analysis of literature suggested 18 accountants' ethics. The research findings found the most important components of Yemeni accountant's ethics are four components, i.e, two for Deliberative Ethics and two for Prescriptive Ethics. The components of Deliberative Ethics are: Deliberative on Protection of Clients, and Deliberative On Conflict Of Interest. In addition, the components of Prescriptive Ethics are: Prescriptive on Independency, and Prescriptive on Duty.